(untitled) (Conferencea, 2023)
Bilingualism, the ability to speak and understand two languages, has long been recognized as a valuable cognitive and sociocultural skill. In our increasingly interconnected world, technology plays a pivotal role in shaping how individuals acquire, use, and maintain their bilingual abilities. This scientific article investigates the intricate relationship between technology and bilingualism, with a particular focus on digital communication platforms and language-learning applications. We explore the ways in which technology can both promote and hinder bilingualism, offering insights into the benefits and challenges posed by these technological advancements.